Assessment of fishery resources and trophic status of Bukidnon Lakes, Central Mindanao, Philippines - Quimpang, Victoria T.; Gregorio, Maridol R. (2014)
The three lakes in Bukidnon, namely Lake Pulangui, Napalit, and Apo, were assessed for their biophysicochemical condition and fisheries status during wet and dry months of 2010-2011. Lake Apo had the highest transparency and depth which are characteristics of an oligotrophic lake. Pulangui Lake had the highest temperature, hardness, dissolved oxygen, pH, CO2, and total alkalinity. Primary production (tons C/ km2/yr) in Pulangi lake was the highest (43,946), followed by Napalit (26,981) and Apo (25,229). Using the Tropic State Index, which is based on chlorophyll a content, Lake Apo was classified as an oligotropic lake while Napalit mesotrophic and Pulangui were identified as eutrophic lake. The three lakes had both the local and exotic fish species, but only in Pulangui the janitor fish was found. Pulangui had the highest fish catch (kg/person/day) (3-15) with 378 fishermen followed by Napalit (3.26-3.90) with 16 fishermen and Apo (0.1) with only two fishermen. Tilapia was the man catch, and gill net was the most commonly used fishing gear. The three lakes have water quality values suitable for fish culture. The estimated potential fish production of the three lakes was higher than their present fish catch. These findings suggest that the present biophysicochemical resources of these lakes may still support aquaculture development.
Keywords: Lake Pulangui, Bukidnon; Lake Napalit (Bukidnon); Lake Apo (Bukidnon); Mindanao studies; Fisheries; Fish production